Diagnostic value of microRNAs derived from exosomes in bronchoalveolar lavage fluid of early‐stage lung adenocarcinoma: A pilot study - Kim, Ji Eun; Eom, Jung Seop; Kim, Won‐young; Jo, Eun Jung; Mok, Jeongha; Lee, Kwangha; Kim, Ki Uk; Park, Hye‐kyung; Lee, Min Ki; Kim, Mi‐hyun (Thoracic cancer, 2018)
Background Low‐dose computed tomography can identify smaller nodules more often than chest radiography in lung screening. However, complications from invasive diagnostic procedures performed to detect nodules are common. Exosomes contain a diverse array of biomolecules that reflect the biological state of the cell from which they are released. The aim of this study was to investigate the diagnostic value of bronchoalveolar lavage (BAL) fluid exosomal microRNAs (miRNAs) for early‐stage lung adenocarcinoma. Methods We evaluated miRNAs (miR‐7, miR‐21, miR‐126, Let‐7a, miR‐17, and miR‐19) known to have diagnostic value for lung adenocarcinoma. Exosomes were isolated from the BAL fluid of control subjects (n = 15) and patients with lung adenocarcinoma (n = 13). Exosomal miRNA was analyzed using a commercial kit containing probes targeting six selected miRNAs. Results were validated via quantitative PCR. Results The presence of miRNAs was confirmed in exosomes from BAL fluid of both lung adenocarcinoma patients and control subjects. miR‐126 (P < 0.001) and Let‐7a (P = 0.015) levels were significantly higher in the BAL fluid of lung adenocarcinoma patients than in control subjects. The BAL fluid miRNA signature was confirmed using an independent set of paired adenocarcinoma and normal tissue samples (n = 4). Lung adenocarcinoma tissues showed increased expression of miR‐126 (P = 0.039) compared to normal tissue samples. Conclusion We identified a close correlation between BAL fluid exosomal miRNAs and tumor miRNAs. BAL fluid exosomal miRNAs obtained through noninvasive methods could serve as diagnostic biomarkers in early‐stage lung adenocarcinoma.